CIENCIA, LEGISLACIÓN Y DISCURSO CONSERVACIONISTA. EL “GERMEN” DE LOS PARQUES NACIONALES EN COSTA RICA: ELEMENTOS CONTEXTUALES Y “MATICES” ANALÍTICOS 1833-1955. - Mc Dermott, Anthony Goebel (2006)
This article explores Costa Rica’s “green image” as a niche with abundant biodiversity and the alleged protection of this natural treasure by the State, through national parks, biological reserves and protected areas. Likewise, this article seeks to understand the various reconstructions made of this protectionist outlook, highlighting the influence of scientific knowledge, political and economic interests, and structural constraints by the State, present in policy-making oriented towards the protection of the natural resources.